KEGIATAN EKSTRAKURIKULER ROHIS HAPIS DALAM PENGEMBANGAN HARGA DIRI (SELF ESTEEM) SISWA DI SMA NEGERI 3 TELUK KERAMAT - Auliati Auliati; Deni Irawan; Enik Sartika (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
The purpose of this study was to find out how HAPIS spiritual extracurriculars can contribute to the development of self-esteem (Self Esteem) of students who take spiritual extracurriculars at SMA Negeri 3 Teluk Keramat. The method used in this study is a qualitative method with a descriptive type of research. In the process of collecting data, researchers used observations, interviews, and documentation. For the data analysis process, researchers used data reduction, data presentation, and conclusions or verification. Meanwhile, to check the validity of the data, researchers used triangulation and member check. Based on the results of the study, it can be concluded that there is a contribution of spiritual extracurricular activities in the development of self-esteem (Self Esteem) of students at SMA Negeri 3 Teluk Keramat through several activities such as Liqo 'Rutin, OBH (Olahraga Together HAPIS), TPQ Fostered Competition, and Outbound. The development that occurs in students shows an increase in self-esteem than before and personality development in a more positive direction. The application of development to students is not only within the scope of the school, but also within the family and society in general.